Rhetorical analysis of descriptions of three Kurdish folk poems - Hasan Tabatabaei; Ferasat Dezhdah (مطالعات زبانی و بلاغی)
Folk tales can be explored from different aspects and dimensions, including rhetorical dimension. In this article, three Kurdish stories of "Shoor Mahmud and Marzingan", "Sheikh Farrokh and Khatun Esti" and "Shaykh Sanan" which have been compiled by Qaderi Fattahi Qaderi have been analyzed and analyzed rhetorically.  The descriptions mentioned in these stories have found special rhetorical effects in accordance with the thoughts and lives of Kurdish speakers. In addition to rhetorical study of the descriptions of these stories, we have adapted them to similar examples in Persian order texts and folk poetry. The result of this analysis and adaptation is that these three Kurdish folk systems are intellectually and linguistically similar to the Khorasani style and are rich in terms of literary types, but in comparison with the examples of Persian order texts, the simile element has a higher frequency in them.Further searches in the rhetorical analysis of these stories showed that the simile-driven rhetoric of these stories has similarities with the rhetoric of folk lyrics, especially folk dobits, but there are also several cases in these stories that are special and unique and there are not about the same authors searching for them in official literature and folk poetry.